PENGARUH KETERAMPILAN DAN KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KEBERHASILAN USAHA KECIL MENENGAH (UMKM) MINUMAN BUBBLE DRINK DI LUBUK PAKAM - prabowo prabowo; Nur'ain Harahap (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2022)
This study aims to determine the effect of skills and abilities of human resources on the success of small and medium enterprises (MSMEs) in Bubble Drink in Lubuk Pakam. This research method uses descriptive and quantitative data. The sample of this study was 52 respondents of small and medium enterprises (MSMEs) with Bubble Drink drinks in Lubuk Pakam. Data was collected by distributing questionnaires. The results of this study indicate that the influence of skills and abilities of human resources has an effect on the success of small and medium enterprises (MSMEs) with Bubble Drink as shown from the results of multiple regression Y = 2.338 + 0.401X1 + 0.453X2 + e. The results obtained from the partial test (t test) of skills on the success of small and medium enterprises (MSMEs) with Bubble Drink drinks obtained t value = 2.544> 1.67 and probability 0.00 at a significance level of 5%, then partially skills have a positive and significant effect on the success of small and medium enterprises (MSMEs) with Bubble Drink drinks in Lubuk Pakam and the results of the t-test of human resource capabilities on the success of small and medium enterprises (MSMEs) with Bubble Drink drinks, the value of tcount = 2.659> 1.67 and probability 0.01 at the significance level 5%, then partially the ability of human resources has a positive and significant effect on the success of small and medium enterprises (MSMEs) in Bubble Drink in Lubuk Pakam. The results of the F test obtained Fcount > Ftable (35.923>3.187) with a probability level (0.01 <0.05), then the skills and abilities of human resources together have a significant effect on the success of small and medium enterprises (MSMEs) in Bubble Drink drinks in Indonesia. Lubuk Pakam.The results obtained from the coefficient of determination (R2) of 0.595, meaning that the skills and abilities of human resources are able to increase the success of small and medium enterprises (MSMEs) in Bubble Drink in Lubuk Pakam. 59.5% and the remaining 40.5% are explained by other variables outside the study.